Examining social support, spirituality, gratitude, and their associations with happiness through self-acceptance - Komarudin, Komarudin; Bukhori, Baidi; Karim, Abdul; Haqqi, Muhammad Fashih Hibatul; Yulikhah, Safitri (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2022)
Happiness is something that every individual yearns for, so an understanding of the factors that influence it is needed. This study aims to test the influence model of social support, spirituality, and gratitude on happiness through self-acceptance. Data collection using the scale of social support, spirituality, gratitude, self-acceptance, and happiness, with a sample of 790 Indonesian students. The data were analyzed using Structural Equation Modeling (SEM) analysis. The structural model showed acceptable goodness of fit. Self-acceptance was demonstrated to significantly serve as a mediating variable in social support, spirituality, and gratitude in relation to happiness. In addition, social support (β = .112, p < .01), gratitude (β = .256, p < .01), spirituality (β = .431, p < .01), and self-acceptance (β = .364, p < .01) had significant positive relationships with happiness. The study has important implications globally for characteristics such as the sample used, especially with regard to the self-acceptance and happiness of university students.